The Impact of Transformational Leadership on Employee Retention: Mediation and Moderation Through Organizational Citizenship Behavior and Communication - Tian, Hongyun; Iqbal, Shuja; Akhtar, Shamim; Qalati, Sikandar Ali; Anwar, Farooq; Khan, Muhammad Aamir Shafique (Frontiers in Psychology, 2020)
This study investigates the impact of transformational leadership on employee retention in SMEs as well as probes the mediating role of organizational citizenship behavior, and the moderating role of communication. Data was collected using convenience sampling from 505 employees of SMEs. Smart PLS structured equation model (PLS-SEM) was used to estimate the various relationships. The findings of the study reveal that there is a positive and significant relationship in transformational leadership and organizational citizenship behavior. Similarly, this study finds a positive and significant relationship in organizational citizenship behavior and employee retention. Besides, organizational citizenship behavior had a positive mediating effect on the relationship between transformational leadership and employee retention. Furthermore, communication positively moderates transformational leadership-organizational citizenship behavior and organizational citizenship behavior-employee retention relationships. Findings revealed that the management of SMEs needs to pay attention to these variables, to retain employees.